Development Strategy of Palm Sugar Product (Case Study: Garunggang Village, Kuala Subdistrict, Langkat District, North Sumatera) - Samuel Simatupang, Donny Ivan; Pakpahan, Helena Tatcher; Tobing, Benni Saputra Lumban (Jurnal Dinamika Sosial Ekonomi, 2025)
This study aims to analyze the internal factors that influence the development of palm sugar products in Garunggang Village, to find out the external factors that influence the development of palm sugar products in Garunggang Village, to analyze the strategy for developing palm sugar products. The determination of the research area was carried out purposively or intentionally, namely in Garunggang Village, Kuala District, Langkat Regency, North Sumatra Province. The sampling method in this study was carried out by census with a sample size of 45 people. Analysis method used was qualitative descriptive and used a SWOT matrix and QSPM. Based on the results of the study, the strength factors are: Palm Sugar is in great demand by consumers, The product has several size variants, The manufacturer collaborates with the North Sumatra UMKM service, The raw materials used are selected quality palm sap, Already has a business license, Affordable price, Has its own brand, Palm Sugar Does not use artificial sweeteners, Product shelf life is 1 year, Attractive and safe packaging. Weakness factors are: Production location is not strategic enough, Online promotion and marketing are not optimal, Sales do not use online marketing media, Limited market segment, Easily damaged if not stored properly. Opportunity factors: Being one of USU's fostered villages, There is training on good product marketing, There is free incentive assistance for labels (composition, Halal, MUI), Technological developments that can help spread information and market faster, Raw materials are easily obtained, Participating in exhibitions held by certain parties. Threat factors: Unstable production of palm sap, The existence of new similar products with cheaper prices, Products are easily imitated, The existence of new and old competitors, Inadequate infrastructure, Unstable internet network connection. Based on the SWOT analysis diagram, it is known that the company's position is in quadrant 1 supporting an aggressive strategy. Based on the order of alternative SWOT strategies, Strength - Opportunity (SO) produces the highest weight. Strength–Opportunity (SO) strategy: use technology for marketing, highlight product benefits, join trainings and exhibitions, and utilize labeling support to expand market reach.